Duodenal neuroendocrine tumor, adenocarcinoma and gastrointestinal stromal tumor in association with neurofibromatosis type 1: An unique occurrence - M A Shamila; P Somasekhara Reddy (Wolters Kluwer Medknow Publications, 2018)
Mixed endocrine-nonendocrine neoplasms are rare tumors and pose challenges in diagnosis and management. Neurofibromatosis-1 (NF-1) patients are known to develop malignancies. Although neuroendocrine tumors and gastro-intestinal stromal tumors are seen in NF-1, its association with adenocarcinoma is rare. The existence of these three entities with NF-1 is extremely rare. NF1 patients presenting with symptoms suggestive of malignancies should alert the physician for a detailed clinical work up. Diagnosis of these malignancies often requires a meticulous histopathological and immunohistochemical examination. We report the first case from Indian experience.